THE EFFECT OF COMBINATION OF OVAPRIM AND OXYTOSIN HORMONES WITH DIFFERENT RATIO ON OVULATION AND THE PENETURE OF BAUNG FISH (Hemibagrus Nemurus) - Rinaldi Rinaldi; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The study was conducted on 26-31 May 2018 at BBI Kurnia Indah Mahato Village KM 37 Tambusai Utara Rokan Hulu Regency. The purpose of this study was to determine the best dose of the effect of the combination of ovaprim and oxytocin hormones with different ratios for ovulation and hatching of fish eggs baung. The method used in this study is the experimental method. The treatments applied in this study were: P0 = Injecting with 100% ovaprim 0.5 ml / kg, P1 = Injecting with 25% oxytocin + 75% ovaprim, P2 = Injecting with 50% oxytocin + 50% ovaprim, P3 = Injecting with 75% oxytocin + 25% ovaprim, P4 = Injection with 100% oxytocin 0.7 ml / kg. The results of this study concluded that ovaprim can be combined with oxytocin to stimulate ovulation and hatching of eggs in baung fish (Hemibagrus nemurus). The best dosage was obtained in P2 treatment (50% ovaprim and 50% oxytocin) which resulted in the fastest latency time of 6 hours 31 minutes, the number of eggs stripping as much as 63 g / parent, and IOS value 3.17%, increase in egg diameter 0.343 mm, egg maturity increase 28%, fertilization value 68%, hatching value 71.3%, and survival value (SR5 days) of 77%. Keywords: Injections, Oxytocin Hormones, Ovaprim Hormones, Baung Fish ((Hemibagrus nemurus))